Kajian Sosiologi Sastra dalam Puisi Sajak Orang Kepanasan Karya W.S Rendra - Yusuf Selamet (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Literary works always contain the author's perspective on reality as a social institution created by the author. These problems are often combined into a view or criticism of life. This certainly describes social life as a reality that occurs in an environment. One type of literary work that contains a view of reality is W.S Rendra's poem entitled "Poem of Hot People". The aim of this research is to determine the effort to explain the social impact of the poem entitled "Poetry of the Overheated People" by W.S Rendra. The poem depicts social and political inequality between the needy class of society and the ruling class of society. Through this research, I hope to make us more sensitive to circumstances and conditions. The reason I chose W.S Rendra's poetry was because the language was very clear and specific. With poetry that uses clear and specific language, the meaning of the content is accurate and complete. The poem is analyzed using the perspective of the social impact that occurs on a phenomenon. The method used in this research is a qualitative method using a literary sociology approach. The technique used is descriptive analysis technique. The researcher sees himself as the only tool. This process involves recording factors related to aspects of social impact as documentation of analysis and as a source of understanding. The results of the research show that the poem "Poetry of Hot People" describes social inequality. Based on these findings, researchers concluded that poetry can be used as a means to criticize existing injustices and express feelings of dissatisfaction with social situations.